BUILDING CHILDREN’S INDEPENDENCE: THE INFLUENCE OF SIGLE PARENT PARENTING IN THE MODERN ERA (JURNAL IBU DAN ANAK, 2025)
This article aims to explore the impact of single-parenting styles on children's independence development in the modern era. The increasing number of families headed by single parents provides a crucial backdrop for understanding parenting dynamics and their effects on children. Through a literature review involving various research and case studies, both in Indonesia and other countries, this article analyzes how parenting styles adopted by single parents, including the provision of responsibility, autonomy support, and communication, correlate with children's levels of independence. The discussion also covers the challenges faced by single parents, such as time constraints and economic pressure, as well as the role of social support and parental psychological well-being in influencing parenting styles and child development. The conclusion of this review highlights that despite the unique challenges in single-parent families, supportive and child-empowerment-focused parenting can effectively foster independence. A supportive social and economic context also plays a crucial role in facilitating the positive development of children in single-parent families.